A single dose of allopregnanolone affects rat ovarian morphology and steroidogenesis. Issue 1 (January 2017) - Pelegrina, Laura Tatiana; Cáceres, Antonella Rosario Ramona; Giuliani, Fernando Alfredo; Asensio, Joana Antonella; Parborell, Fernanda; Laconi, Myriam Raquel
Abstract : Allopregnanolone, a progesterone metabolite, is one of the best characterized neurosteroids. In a dose that mimics serum levels during stress, allopregnanolone inhibits sexual receptivity and ovulation and induces a decrease in luteinizing hormone levels. The aim of this work was to examine the effect of an intracerebroventricular administration of allopregnanolone on ovarian morphophysiology; serum and tissue levels of progesterone and estrogen; and enzymatic activity of 3β-hydroxysteroid dehydrogenase, 20α-hydroxysteroid dehydrogenase and 3α-hydroxysteroid oxido-reductase in the ovary and in the medial basal hypothalamus on the morning of estrus. Ovarian morphology was analyzed under light microscopy. The hormone assays were performed by radioimmunoassay. The enzymatic activities were measured by spectrophotometric analysis. The morphometric analysis revealed that, in allopregnanolone-treated animals, the number of secondary and Graafian follicles was decreased, whereas that of atretic follicles and cysts was significantly increased. Some cysts showed luteinized unruptured follicles. There were no differences in the number of tertiary follicles or corpora lutea in comparison with the corresponding control groups. In allopregnanolone-treated animals, progesterone serum levels were increased, whereas ovarian progesterone levels were decreased. Moreover, 3β-HSD and 3α-HSOR enzymatic activities were increased in the medial basal hypothalamus, whereas ovarian levels were decreased. The enzyme 20α-hydroxysteroid dehydrogenase showed the opposite profile. The results of this study showed that allopregnanolone interferes on ovarian steroidogenesis and ovarian morphophysiology in rats, providing a clear evidence for the role of this neurosteroid in the control of reproductive function under stress situations. Free Spanish abstract: A Spanish translation of this abstract is freely available athttp://www.reproduction-online.org/content/153/1/75/suppl/DC1 .